Women at Indiana University : 150 Years of Experiences and Contributions - Walton, Andrea, 1959- (Book collections on Project MUSE., 2022)
"The first in-depth look at how women have shaped the history and legacy of Indiana University. Women first enrolled at Indiana University in 1867. In the following years they would leave an indelible mark on this Hoosier institution. However, until now their stories have been underappreciated, both on the IU campus and by historians, who have paid them little attention. Women at Indiana University draws together 15 snapshots of IU women's experiences and contributions to explore essential questions about their lives and impact. What did it mean to write the petition for women's admission or to become the first woman student at an all-male university? To be a woman of color on a predominantly white campus? To balance work, studies, and commuting, entering college as a non-traditional student? How did women contribute to their academic fields and departments? How did they tap opportunities, confront barriers, and forge networks of support to achieve their goals? Women at Indiana University not only opens the door to a more inclusive and accurate understanding of IU's past and future, but also offers greater visibility for Hoosier women in our larger understanding of women in American higher education"--